The relationship between heterozygosity of Pygospio elegans and their parasite infection - Rony, Irin (2021)
At the individual level, the increased risk of parasitic infection is correlated with both host-parasitic interaction and host heterozygosity. On the other hand, hosts can respond to different parasites depending on parasite virulence or host susceptibility. I investigated if patterns of parasitic infection were influenced by heterozygosity of the host, Pygospio elegans, a polychaete worm. Samples of the host were collected from three sites: Cramond, Scotland, and Herslev and Vellerup, Denmark; each at two times: November 2018 and November 2019. Based on previous studies, these populations were expected to differ in heterozygosity. Because more heterozygous individuals could have a more varied response to parasites, I hypothesized that more heterozygous individuals would have fewer parasites than would homozygous individuals. I amplified seven microsatellite loci in multiplex reactions and genotyped individual hosts from each location and sampling time to determine individual heterozygosity. In addition, ddPCR quantification of apicomplexan parasite infection was used to determine individual’s parasite load of an unidentified agamococcidian species. The association between genetic diversity and parasitic load was then investigated. Populations sampled in 2019 showed more heterozygosity than those sampled in 2018. Prevalence of the parasite did not differ between populations or years. The infection load of the agamococcidian was significantly higher in Scotland in both years than in the Danish populations, however, no correlation was found between individual heterozygosity and parasite load. The result suggests that regardless the infection load, an individual’s heterozygosity might not be relevant for parasite susceptibility or the tolerance for these interacting species. Other parasite species of Pygospio elegans can be studied in future to see if the results vary.